2021
DOI: 10.23887/jere.v5i4.34019
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Materials Needs: Student Worksheets in Exposition Text Learning

Abstract: Indonesian language teachers in schools lack teaching materials. Even teachers don't have HOTS-oriented open materials. It will impact students who have difficulty in learning because they do not have learning resources. Professional educators must be able to develop teaching materials to address the learning objectives of the 2013 Curriculum in any learning situation. The readiness of teachers to carry out the teaching and learning process can be assisted by applying teaching materials that are by the 2013 cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Based on the explanation above, it can be concluded that a teaching material is needed that can implement the 2013 curriculum for special education by emphasizing and improving affective, cognitive, and psychomotor skills. Teaching materials are one of the important learning components to be developed by educators so that teaching and learning activities remain effective and productive (Sagitari et al, 2021;Indrianto & Kurniawati, 2020) which displays a complete figure of the competencies that students will master (Fajri, 2018). Lu Feikui, a modern Chinese educator, clearly pointed out in the article "Declaration of Zhonghua Book Company" that the foundation of a nation is education, while the foundation of education is teaching materials (Yao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the explanation above, it can be concluded that a teaching material is needed that can implement the 2013 curriculum for special education by emphasizing and improving affective, cognitive, and psychomotor skills. Teaching materials are one of the important learning components to be developed by educators so that teaching and learning activities remain effective and productive (Sagitari et al, 2021;Indrianto & Kurniawati, 2020) which displays a complete figure of the competencies that students will master (Fajri, 2018). Lu Feikui, a modern Chinese educator, clearly pointed out in the article "Declaration of Zhonghua Book Company" that the foundation of a nation is education, while the foundation of education is teaching materials (Yao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%